Effect of Cannabidiol (CBD) oil on acne (Research, Society and Development, 2021)
O Cannabidiol is a non-psychoactive cannabinoid isolated from Cannabis sativa which, due to its alleged beneficial properties and therapeutic potential, and a topic increasingly discussed as decriminalization and legalization of these products continue to expand, has recently raised considerable interest attention of the scientific community. And with little evidence in the literature, the main objective of this study was to investigate the administration of CBD, with a particular focus on the influence of aspects related to anti-inflammatory, antimicrobial properties on acne. However, the current role of CBD in the treatment of dermatological conditions remains to be defined. We performed a review of the current literature to determine the skin applications of cannabinoids. After performing our analysis, we found that cannabinoid products have the potential to treat a variety of skin conditions, including acne. However, most of the data available on these compounds are preclinical and there is a corresponding lack of high-quality controlled studies evaluating their effects.With the chemistry and pharmacology of CBD, and with various molecular targets, including cannabinoid receptors and the endocannabinoid system with which they eventually interact, have been studied extensively. This article provides an update on advances in CBD research to date and potential areas for future exploration.